THE IMPACT OF INSTITUTION IMAGE AND STUDENT SATISFACTION TO WORD OF MOUTH - Mulyana, Andy; Ayuni, Devi (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2015)
In the recent years a tremendous growth has been observed in the Indonesia higher education institutions (HEI). The growth in the number of HEI in year 2009 – 2013 increased from 1.382 to 3.151. The increase in the number of HEI in Indonesia has resulted in the industry becoming very competitive. The situation call for HEIs to focus on establishing a strong institution image and providing student satisfaction to secure their positive word of mouth. A conceptual framework is proposed that investigates the impact of institution image and student satisfaction on word of mouth (WOM). Survey was employed and respondents were from the students of Indonesian Open University (Universitas Terbuka = UT). There were 155 usable questionnaires to analyze descriptive statistics, realibility, validity and structural equation modeling (SEM). The research found that institution image and student satisfaction significantly affects WOM and that image exerts a stronger influence on WOM than satisfaction. Therefore, UT as a service firm has to focus on these factors in order to built a long-term and mutally profitability relationship with a student and create positive WOM as competitive advantage.